Estimating the firm's labor supply curve in a new monopsony framework: school teachers in Missouri - Michael R. Ransom; David P. Sims (Institute for the Study of Labor (IZA), 2009)
In the context of certain dynamic models, it is possible to infer the elasticity of labor supply to the firm from the elasticity of the quit rate with respect to the wage. Using this property, we estimate the average labor supply elasticity to public school districts in Missouri. We take advantage of the plausibly exogenous variation in pre-negotiated district salary schedules to instrument for actual salary. Instrumental variables estimates lead to a labor supply elasticity estimate of about 3.7, suggesting the presence of significant market power for school districts, especially over more experienced teachers. The presence of monopsony power in this labor market may be partially explained by institutional features of the teacher labor market.
urn:nbn:de:101:1-2009082000
Keywords: J42; J63; 330; Labor monopsony; teachers; Lehrkräfte; Arbeitsangebot; Elastizität; Schule; Monopson; Schätzung; Missouri (Staat)